ETHNOBOTANICAL STUDY OF RAJABIYAH TRADITION - Nurul Mufidah, Elyza Rohman; Darmawan, Ericka; Prajoko, Setiyo (Prodi Pendidikan Biologi, FPMIPATI, Universitas PGRI Semarang, 2025)
Indonesia is a country with diverse tribes, cultures, and customs in each region. The Rajabiyah Tradition is a local culture of the Prawoto Village community in Pati Regency, the implementation of which is related to the use of surrounding plants, both for traditional rituals and religious rituals. This study aims to determine the ethnobotanical profile of the Rajabiyah Tradition which includes the istighosah procession, grave pilgrimage, buka luwur, washing of grave banners, luwur procession and cultural procession, and tabligh akbar. This study is a combined study, namely ethnographic research with a qualitative descriptive and quantitative descriptive research approach. Samples were taken using snowball sampling and purposive sampling techniques. Data collection was carried out through semi-structured interviews. Interviews were conducted with 30 informants who were 1 village official, 1 traditional leader, 1 grave caretaker, and 1 community leader and 26 residents of Prawoto Village. The results of the study obtained 49 types of plants used in each Rajabiyah Tradition procession which were grouped into 26 diversities of order levels. The most widely used order is the Zingiberales order and the most widely used part of the plant is the fruit. Each plant used has a different aspect of meaning which is the good hope of the people of Prawoto Village.